Nursing interventions in oral administration of Cyclosporine - Savić Maja (Association of Nurses Technicians and Midwives, 2023)
Cyclosporine or cyclosporine A is an immunosuppressive medicine used after solid organ transplantation -heart, lungs, liver, pancreas, kidney and bone marrow - to prevent organ transplant rejection and to ensure proper functioning of the transplanted organ or bone marrow. It is used in the treatment of a wide range of autoimmune diseases in various branches of medicine -hematology, ophthalmology, dermatology, nephrology, rheumatology and gastroenterology. The discovery of cyclosporine and decades of its use have led to a revolution in transplant medicine. It can be administered intravenously, orally -capsules and oral solutions, intraocularly and by inhalation. Given the successful administration of cyclosporine is the most important factor in effectual therapeutic effect, the nurse must successfully perform all the stages of the administration of oral forms of this drug, which are: medicine storage, preparation for medicine administration, medicine administration, waste disposal and providing education of the patient and family members. During the performance of all these stages, ac-cording to the health care protocol, the nurse must demonstrate dexterity, skill, confidence and a professional attitude towards the patient, while respecting all ethical principles. A successful administration of cyclosporine requires a team approach involving the doctor, nurse, patient and family members, continual professional training, keeping pace with innovations in this field and constant work on improving communication skills.